Good news to the poor : the challenge to the Church - Kim, Sebastian C. H.; Marak, Krickwin C.; Union Biblical Seminary (Pune, India). Centre for Mission Studies; I.S.P.C.K. (Organization) (Delhi : Published jointly by Indian Society for Promoting Christian Knowledge and Centre for Mission Studies, Union Biblical Seminary, 1997)
Contributed articles.
Includes bibliographical references.
Keywords: Poverty -- Religious aspects -- Christianity; Church work with the poor -- India